Chronic kidney disease impairs prognosis in electrical storm - Weidner, Kathrin; Behnes, Michael; Schupp, Tobias; Hoppner, Jorge; Ansari, Uzair; Müller, Julian; Lindner, Simon; Borggrefe, Martin; Kim, Seung‑Hyun; Huseynov, Aydin; Ellguth, Dominik; Akın, Muharrem; et al. (Journal of interventional cardiac electrophysiology, 2022)
The study sought to assess the prognostic impact of chronic kidney disease (CKD) in patients with electrical storm (ES). ES represents a life-threatening heart rhythm disorder. In particular, CKD patients are at risk of suffering from ES. However, data regarding the prognostic impact of CKD on long-term mortality in ES patients is limited.
Online veröffentlicht: 3. January 2021
Gesehen am 26.01.2023